2007
DOI: 10.1111/j.1529-8817.2007.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas raudensis (UWO 241), Chlorophyceae, exhibits the capacity for rapid D1 repair in response to chronic photoinhibition at low temperature1

Abstract: Maximum photosynthetic capacity indicates that the Antarctic psychrophile Chlamydomonas raudensis H. Ettl UWO 241 is photosynthetically adapted to low temperature. Despite this finding, C. raudensis UWO 241 exhibited greater sensitivity to lowtemperature photoinhibition of PSII than the mesophile Chlamydomonas reinhardtii P. A. Dang. However, in contrast with results for C. reinhardtii, the quantum requirement to induce 50% photoinhibition of PSII in C. raudensis UWO 241 (50 lmol photons) was comparable at eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…This is in agreement with previous studies that show that UWO 241 exhibits rapid rates of D1 repair and recovery from photoinhibition at low temperatures (Pocock et al, 2007). Consequently, it appears that STT8 is present and active in UWO 241.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is in agreement with previous studies that show that UWO 241 exhibits rapid rates of D1 repair and recovery from photoinhibition at low temperatures (Pocock et al, 2007). Consequently, it appears that STT8 is present and active in UWO 241.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with the fact that temperature-response curves for light-saturated rates of CO 2 -saturated oxygen evolution indicate that UWO 241 photosynthesizes maximally at 8°C at rates that are comparable to rates of the mesophile, C. reinhardtii, grown and measured at 29°C (Pocock et al, 2007). Although UWO 241 exhibits a low quantum requirement for photoinhibition and the degradation of the PSII reaction center polypeptide D1 (PsbA), this is complemented by a rapid, light-dependent recovery of PSII photochemistry associated with the de novo biosynthesis of D1 at low temperature (Pocock et al, 2007). Thus, this psychrophile appears to be photosynthetically adapted to growth at low temperature (Pocock et al, 2007).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Two decades of intensive laboratory studies on axenic isolates of this organism have revealed that the photochemical apparatus is finely adjusted to the extremely stable low light and low temperature environment from which it was isolated (Morgan‐Kiss et al ,, , ; Morgan‐Kiss and Dolhi ). Evolution of a highly efficient photochemical apparatus in this species has been as a consequence of a loss of multiple acclimatory responses to environmental variability (Morgan‐Kiss et al ,; Pocock et al ; Szyszka et al ). Experiments on acclimation to light quality showed that C. raudensis exhibits a novel requirement for blue light and reverts to a downregulated photochemical state under dark incubation or in the presence of red light (Morgan‐Kiss et al ).…”
mentioning
confidence: 99%